2012
DOI: 10.1503/cmaj.111619
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative age on diagnosis and treatment of attention-deficit/hyperactivity disorder in children

Abstract: Research CMAJ Background:The annual cut-off date of birth for entry to school in British Columbia, Canada, is Dec. 31. Thus, children born in December are typically the youngest in their grade. We sought to determine the influence of relative age within a grade on the diagnosis and pharmacologic treatment of attentiondeficit/ hyperactivity disorder (ADHD) in children. Methods:We conducted a cohort study involving 937 943 children in British Columbia who were 6-12 years of age at any time between Dec. 1, 1997, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
129
2
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 26 publications
17
129
2
20
Order By: Relevance
“…Several studies (Elder, 2010; Evans, Morrill, & Parente, 2010; Halldner et al, 2014; Morrow et al, 2012; Zoëga, Valdimarsdóttir, & Hernández-Díaz, 2012) showed that relative age is a significant determinant of ADHD diagnosis and treatment. Overall, the youngest children in class are twice as likely as their classmates to receive a diagnosis of ADHD and medication.…”
Section: Birth Month Mattersmentioning
confidence: 99%
“…Several studies (Elder, 2010; Evans, Morrill, & Parente, 2010; Halldner et al, 2014; Morrow et al, 2012; Zoëga, Valdimarsdóttir, & Hernández-Díaz, 2012) showed that relative age is a significant determinant of ADHD diagnosis and treatment. Overall, the youngest children in class are twice as likely as their classmates to receive a diagnosis of ADHD and medication.…”
Section: Birth Month Mattersmentioning
confidence: 99%
“…As 1 See for example, Bedard and Dhuey (2006), Datar (2006), Crawford et al (2007), Puhani and Weber (2007), McEwan and Shapiro (2008), Lubotsky (2009), Smith (2009), Kawaguchi (2011), Cook andKang (2016), Lubotsky and Kaestner (2016), McAdams (2016), Landerso et al (2017b) and Attar and Cohen-Zada (2017). Some other outcomes investigated in this literature include high school leadership (Dhuey and Lipscomb 2008), pre-academic university tracks and enrollment in selective universities (Bedard and Dhuey 2006), and disability identification and special education (Dhuey and Lipscomb 2010;Elder and Lubotsky 2009;Evans et al 2010;Morrow et al 2012) 2 For instance, Fredriksson and Ockert (2014) and Kawaguchi (2011) find that older children at school entry earn higher wages; and Du et al (2012) find that they are more likely to be a corporate CEO. In contrast, Black et al (2011), Dobkin and Ferreira (2010), and Fertig and Kluve (2005) find no such long-term wage effects.…”
Section: Introductionmentioning
confidence: 99%
“…In evaluating the importance of overdiagnosis in a condition at the population level, we propose focusing on the frequency of overdiagnoses relative [83][84][85] Although this phenomenon has been labeled overdiagnosis, one could argue that misdiagnosis is more appropriate (ie, immaturity is misdiagnosed as ADHD).…”
Section: Overdiagnosis In Childrenmentioning
confidence: 99%